Functionalized PEG hydrogels through reactive dip-coating for the formation of immunoactive barriers - Hume, Patrick S. (2011)
Influencing the host immune system via implantable cell-delivery devices has the potential to reduce inflammation at the transplant site and increase the likelihood of tissue acceptance. Towards this goal, an enzymatically-initiated, dip-coating technique is adapted to fabricate conformal hydrogel layers and to create immunoactive polymer coatings on cell-laden poly(ethylene glycol) (PEG) hydrogels. Glucose oxidase (GOx)-initiated dip coatings enable the rapid formation of uniform, PEG-based coatings on the surfaces of PEG hydrogels, with thicknesses up to 500 μm where the thickness is proportional to the reaction time. Biofunctional coatings were fabricated by thiolating biomolecules that were subsequently covalently incorporated into the coating layer via thiol-acrylate copolymerization. The presence of these proteins was verified via fluorescent confocal microscopy and a modified ELISA, which indicated IgG concentrations as high as 13±1 ng / coated cm(2) were achievable. Anti-Fas antibody, known to induce T cell apoptosis, was incorporated into coatings, with or without the addition of ICAM-1 to promote T cell interaction with the functionalized coating. Jurkat T cells were seeded atop functionalized coatings and the induction of apoptosis was measured as an indicator of coating bioactivity. After 48 hours of interaction with the functionalized coatings, 61±9% of all cells were either apoptotic or dead, compared to only 18±5% of T cells on non-functionalized coatings. Finally, the cytocompatibility of the surface-initiated GOx coating process was confirmed by modifying gels with either encapsulated β-cells or 3T3 fibroblasts within a gel that contained a PEG methacrylate coating.